Иммуностимулирующая CpG-ДНК: перспективы клинического применения в онкологии - Олишевский, С.В.; Козак, В.В.; Яниш, Ю.В.; Рыбалко, С.Л.; Шляховенко, В.А. (Iнститут експериментальної патології, онкології і радіобіології ім. Р. Є. Кавецького, 2006)
Представлены сведения о новом перспективном направлении в иммунотерапии рака — применении ДНК, обогащенной неметилированными CpG-мотивами. Приведены данные об иммуностимулирующих свойствах CpG-ДНК, путях передачи сигнала в клетке и классификации синтетических CpG-олигодезоксинуклеотидов (CpG-ОДН). Рассмотрены вопросы перспективности применения CpG-ОДН для иммунотерапии больных со злокачественными новообразованиями. The review presents information about the new promising area in tumor immunotherapy, i.e. application of DNA enriched with non-methylated CpG-motives. Data is presented on the immunostimulatory characteristics of CpG DNA and ways of cell signaling, as well as about classification of synthetic CpG-oligodeoxydeoxynucleotides (CpG-ODN). The prospects for application of CpG-ODN for immunotherapy of patients with malignant neoplasm are discussed.